Owner-managed closed it companies in Croatia : corporate governance and IP protection issues - Mutabžija, Jasmina, pravnica (Array, 2019)
Intellectual property protection is an important ingredient in the market success of knowledge-intensive enterprises operating in the information technology industry. The governance and the extent of protection of intellectual property related to software often seem to be connected to certain characteristics of an enterprise, such as its type and size. By analyzing the publicly available data, the author identifies various patterns primarily concerning the structure of ownership and management of the software enterprises in Croatia. The analysis reveals that all of the top 500 software enterprises according to revenue are closed, with the overwhelming majority being owner-managed and small or micro-sized. This would suggest that most software enterprises in Croatia are passive when it comes to their intellectual property. In relation to this, the author describes three profiles of enterprises depending on their attitude towards the governance of intellectual property. The author also formulates and explores four possible complementary approaches to the protection of intellectual property, both legal and non-legal, in addition to discussing various types of intellectual property rights with the aim of identifying those that are more suitable for the protection of different types of software.